New azodyrecins identified by a genome mining-directed reactivity-based screening - Choirunnisa, Atina Rizkiya; Arima, Kuga; Abe, Yo; Kagaya, Noritaka; Kudo, Kei; Suenaga, Hikaru; Hashimoto, Junko; Fujie, Manabu; Satoh, Noriyuki; Shin-ya, Kazuo; Matsuda, Kenichi; Wakimoto, Toshiyuki (Beilstein Journal of Organic Chemistry, 2022)
Only a few azoxy natural products have been identified despite their intriguing biological activities. Azodyrecins D–G, four new analogs of aliphatic azoxides, were identified from two Streptomyces species by a reactivity-based screening that targets azoxy bonds. A biological activity evaluation demonstrated that the double bond in the alkyl side chain is important for the cytotoxicity of azodyrecins. An in vitro assay elucidated the tailoring step of azodyrecin biosynthesis, which is mediated by the S-adenosylmethionine (SAM)-dependent methyltransferase Ady1. This study paves the way for the targeted isolation of aliphatic azoxy natural products through a genome-mining approach and further investigations of their biosynthetic mechanisms.
Keywords: biosynthesis; methyltransferase; natural azoxides; reactivity-based screening; Streptomyces

(untitled) - Wibowo, M.; Ding, L. (J. Nat. Prod., 2020)

(untitled) - Blair, L. M.; Sperry, J. (J. Nat. Prod., 2013)

(untitled) - Le Goff, G.; Ouazzani, J. (Bioorg. Med. Chem., 2014)

(untitled) - Langley, B. W.; Lythgoe, B.; Riggs, N. V. (J. Chem. Soc., 1951)

(untitled) - Hughes, C. C. (Nat. Prod. Rep., 2021)

(untitled) - Harris, L. A.; Mitchell, D. A. (Methods Enzymol., 2022)

(untitled) - Harris, L. A.; Saint-Vincent, P. M. B.; Guo, X.; Hudson, G. A.; DiCaprio, A. J.; Zhu, L.; Mitchell, D. A. (ACS Chem. Biol., 2020)

(untitled) - Huang, Y.-B.; Cai, W.; Del Rio Flores, A.; Twigg, F. F.; Zhang, W. (Anal. Chem. (Washington, DC, U. S.), 2020)

(untitled) - Moss, N. A.; Seiler, G.; Leão, T. F.; Castro‐Falcón, G.; Gerwick, L.; Hughes, C. C.; Gerwick, W. H. (Angew. Chem., Int. Ed., 2019)

(untitled) - Back, D.; Shaffer, B. T.; Loper, J. E.; Philmus, B. (J. Nat. Prod., 2022)

(untitled) - Matsuda, K.; Arima, K.; Akiyama, S.; Yamada, Y.; Abe, Y.; Suenaga, H.; Hashimoto, J.; Shin-ya, K.; Nishiyama, M.; Wakimoto, T. (J. Am. Chem. Soc., 2022)

(untitled) - Guo, Y.-Y.; Li, H.; Zhou, Z.-X.; Mao, X.-M.; Tang, Y.; Chen, X.; Jiang, X.-H.; Liu, Y.; Jiang, H.; Li, Y.-Q. (Org. Lett., 2015)

(untitled) - Guo, Y.-Y.; Li, Z.-H.; Xia, T.-Y.; Du, Y.-L.; Mao, X.-M.; Li, Y.-Q. (Nat. Commun., 2019)

(untitled) - Franke, J.; Ishida, K.; Ishida-Ito, M.; Hertweck, C. (Angew. Chem., Int. Ed., 2013)

(untitled) - Parry, R. J.; Li, W. (Arch. Biochem. Biophys., 1997)

(untitled) - Parry, R. J.; Li, W. (J. Biol. Chem., 1997)

(untitled) - Li, H.; Forson, B.; Eckshtain-Levi, M.; Valentino, H.; Martín del Campo, J. S.; Tanner, J. J.; Sobrado, P. (Biochemistry, 2021)

(untitled) - Garg, R. P.; Qian, X. L.; Alemany, L. B.; Moran, S.; Parry, R. J. (Proc. Natl. Acad. Sci. U. S. A., 2008)

(untitled) - Garg, R. P.; Ma, Y.; Hoyt, J. C.; Parry, R. J. (Mol. Microbiol., 2002)

(untitled) - Nindita, Y.; Cao, Z.; Fauzi, A. A.; Teshima, A.; Misaki, Y.; Muslimin, R.; Yang, Y.; Shiwa, Y.; Yoshikawa, H.; Tagami, M.; Lezhava, A.; Ishikawa, J.; et al. (Sci. Rep., 2019)

(untitled) - Wibowo, M.; Gotfredsen, C. H.; Sassetti, E.; Melchiorsen, J.; Clausen, M. H.; Gram, L.; Ding, L. (J. Nat. Prod., 2020)

(untitled) - Taylor, K. G.; Riehl, T. (J. Am. Chem. Soc., 1972)

(untitled) - Ding, L.; Ndejouong, B. L. S. T.; Maier, A.; Fiebig, H.-H.; Hertweck, C. (J. Nat. Prod., 2012)

(untitled) - Kunitake, H.; Hiramatsu, T.; Kinashi, H.; Arakawa, K. (ChemBioChem, 2015)

(untitled) - Stevens, C. L.; Gillis, B. T.; French, J. C.; Haskell, T. H. (J. Am. Chem. Soc., 1956)

(untitled) - Haskell, T. H.; Ryder, A.; Bartz, Q. R. (Antibiot. Chemother., 1954)

(untitled) - Manderscheid, N.; Helaly, S. E.; Kulik, A.; Wiese, J.; Imhoff, J. F.; Fiedler, H.-P.; Süssmuth, R. D. (J. Antibiot., 2013)

(untitled) - Fukumoto, A.; Murakami, C.; Anzai, Y.; Kato, F. (J. Antibiot., 2016)

(untitled) - Takahashi, Y.; Nakayama, M.; Watanabe, I.; Deushi, T.; Ishiwata, H.; Shiratsuchi, M.; Otani, G. (J. Antibiot., 1989)

(untitled) - McGahren, W. J.; Kunstmann, M. P. (J. Am. Chem. Soc., 1969)

(untitled) - Yamato, M.; Iinuma, H.; Naganawa, H.; Yamagishi, Y.; Hamada, M.; Masuda, T.; Umezawa, H.; Abe, V.; Hori, M. (J. Antibiot., 1986)

WO Pat. Appl. - Nakano, H.; Hara, M.; Katsuyama, T.; Uozaki, Y.; Gomi, K. (Compound DC0110, 1993)

(untitled) - Garg, R. P.; Alemany, L. B.; Moran, S.; Parry, R. J. (J. Am. Chem. Soc., 2009)

(untitled) - Garg, R. P.; Gonzalez, J. M.; Parry, R. J. (J. Biol. Chem., 2006)